Recognition and validation of prior learning of adult immigrants from sub-Saharan Africa. The biographical-narrative approach as element of personalization - Angeloni, Brigida (Formazione & insegnamento, 2020)
The presence of people from non-European countries in Italy is now a consolidated reality. Their inclusion in our cultural, social and economic framework requires a series of interventions that guarantee respect for the rights of these people and that can facilitate the re-acquisition of an autonomous and dignified life, in order to allow the realization of the migration project and full integration in our country. The professional placement and in education, university and professional training courses is a key element to strengthen the sense of empowerment of immigrants. But it is equally important that employment and training opportunities are related to the competences already possessed. Currently Italian reception system and public services are rarely able to accompany an immigrant towards the recognition of previous competences and learning. It is necessary to start an innovation in the system of validation and certification of competences, which starts from what already exists in terms of experiences achieved on other targets, but which adapts languages, tools and paths to the needs of people riding on different cultures, ensuring therefore greater accessibility to these procedures, in a fair, sustainable and inclusive way.